Genistein—Opportunities Related to an Interesting Molecule of Natural Origin - Ewa Garbiec; Judyta Cielecka-Piontek; Magdalena Kowalówka; Magdalena Hołubiec; Przemysław Zalewski (Molecules, 2022)
Nowadays, increasingly more attention is being paid to a holistic approach to health, in which diet contributes to disease prevention. There is growing interest in functional food that not only provides basic nutrition but has also been demonstrated to be an opportunity for the prevention of disorders. A promising functional food is soybean, which is the richest source of the isoflavone, genistein. Genistein may be useful in the prevention and treatment of such disorders as psoriasis, cataracts, cystic fibrosis, non-alcoholic fatty liver disease and type 2 diabetes. However, achievable concentrations of genistein in humans are low, and the use of soybean as a functional food is not devoid of concerns, which are related to genistein’s potential side effects resulting from its estrogenic and goitrogenic effects.